Applicability of bio-synthesized nanoparticles in fungal secondary metabolites products and plant extracts for eliminating antibiotic-resistant bacteria risks in non-clinical environments - Kamaruzaman, Nur Hazirah; Mohd Noor, Nur Nabilah; Radin Mohamed, Radin Maya Saphira; Al-Gheethi, Adel; Ponnusamy, Senthil Kumar; Sharma, Ajit; N. Vo, Dai-Viet (Elsevier, 2022)
The abundance of antibiotic-resistant bacteria in the prawn pond effluents can substantially impact the natural environment. The settlement ponds, which are the most common treatment method for farms wastewater, might effectively reduce the suspended solids and organic matter. However, the method is insufficient for bacterial inactivation. The current paper seeks to highlight the environmental issue associated with the distribution of antibiotic resistant bacteria (ARB) from prawn farm wastewater and their impact on the microbial complex community in the surface water which receiving these wastes. The inactivation of antibiotic-resistant bacteria in prawn wastewater is strongly recommended because the presence of antibiotic-resistant bacteria in the environment causes water pollution and public health issues. The nanoparticles are more efficient for bacterial inactivation. They are widely accepted due to their high chemical and mechanical stability, broad spectrum of radiation absorption, high catalytic activity, and high antimicrobial activity. Many studies have examined the use of fungi or plants extract to synthesis zinc oxide nanoparticles (ZnO NPs). It is evident from recent papers in the literature that green synthesized ZnO NPs from microbes and plant extracts are non-toxic and effective. ZnO NPs inactivate the bacterial cells as a function for releasing reactive oxygen species (ROS) and zinc ions. The inactivation of antibiotic-resistant bacteria tends to be more than 90% which exhibit strong antimicrobial behavior against bacterial species.